2001
DOI: 10.1007/s004390100575
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the alpha1-antichymotrypsin (ACT) gene promoter: effect on expression in transfected glial and liver cell lines and plasma ACT concentrations

Abstract: Alpha1-antichymotrypsin (ACT: new identification SERPINA3) is a member of the serine proteinase inhibitor (serpin) gene family and biochemically has been shown to be a constituent of the senile plaques of Alzheimer's disease. We describe a polymorphism (G-->T) in the promoter region of the ACT gene with the T allele being associated with a 22% increase in the mean plasma ACT concentrations. By reporter gene studies, the T allele is consistently associated with higher mean basal expression in both the human liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…An alternative explanation for the current observation is that the ACT signal peptide polymorphism may be in linkage disequilibrium with a functional variant either within the ACT gene or in a nearby gene. Recently, a polymorphisms in the ACT promoter (−51G>T) has been described that affects ACT expression in transfected glial cell lines [15] and AD risk [10]. We found that although this polymorphism is in strong linkage disequilibrium with the signal peptide polymorphism, it was not associated with either the risk or AAO of AD (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…An alternative explanation for the current observation is that the ACT signal peptide polymorphism may be in linkage disequilibrium with a functional variant either within the ACT gene or in a nearby gene. Recently, a polymorphisms in the ACT promoter (−51G>T) has been described that affects ACT expression in transfected glial cell lines [15] and AD risk [10]. We found that although this polymorphism is in strong linkage disequilibrium with the signal peptide polymorphism, it was not associated with either the risk or AAO of AD (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown that cells transfected with G or T alleles of the promoter region of SERPINA3 G/T polymorphism, being in complete linkage disequilibrium with a signal peptide A/T polymorphism, display different expression of SERPINA3. 4 The effect of G/T polymorphism on luciferase reporter gene activity in Hep G2 and T98G cells shows that both basal and stimulated by oncostatin M expression of SERPINA3 in cells transfected with T allele is significantly higher compared with cells transfected with G allele.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 However, some studies have not shown a relationship between the polymorphism and levels of SERPINA3. 17 These discrepancies may be attributable to the fact that SERPINA3 levels are highly variable and sensitive to different peripheral inflammatory conditions, which may influence the function of SERPINA3 AA, AT, and TT proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The À51G/T polymorphism (rs1884082, named ACT4) in the ACT promoter was directly associated with altered gene expression and the TT genotype was associated with an increased risk of early onset AD. [13][14][15][16] Other reports suggested that the TT genotype was associated with late onset AD, whereas the single nucleotide polymorphism (SNP) was not associated with AD. 17,18 To our knowledge, there have been no reports on ACT regulatory region polymorphism in Chinese patients with AD.…”
Section: Introductionmentioning
confidence: 97%